Review of Maternal Mortality in Ethiopia: A Story of the Past 30 Years - Berhan, Yifru (Ethiop J Health Sci, 2014)
BACKGROUND: Ethiopia is one of the six countries which have contributed to more than 50% of all maternal deaths across the world. This country has adopted the millennium development goals (MDGs) including reducing the maternal mortality by three-quarter, and put improvement in maternal health as one of the health sector development program (HSDP) performance indicators. The purpose of this study was to review the maternal mortality ratio (MMR) in Ethiopia in the past 30 years using available literature. METHODS: A computer based literature search in the databases of MEDLINE, PubMed, HINARI, EBASE, MEASURE DHS, The Cochrane Library, Google Search and Google Scholar was carried out. Manual search for local articles that are not available electronically in full document were also conducted. Eighteen data sources (3 nationally representative surveys, 2 secondary data analyses, 5 small scale community based studies, and 8 hospital based studies) were included in the review. The results of this review are presented in the form of line and stock graphs. RESULTS: The national maternal mortality trend estimated by the central statistics agency of Ethiopia, The Institute for Health Metrics and Evaluation, WHO and other UN agencies showed inconsistent results. Similarly, although there were marked variations in the 95% confidence intervals among individual studies, the small scale community based and hospital based studies have shown that there has been no significant change in maternal mortality over the last three decades. A 22-year cohort analysis from Atat Hospital is the only evidence that demonstrated a very significant drop in maternal mortality among mothers who were kept in the maternity waiting area before the onset of labor. CONCLUSION: Although the MDG and HSDP envisaged significant improvement in maternal health by this time, this review has shown that the performances are still far from the target. The multisectoral huge investment by the Ethiopian Government is a big hope to reduce the maternal mortality by three-quarters in the near future beyond 2015.